Repellent Efficacy of Eucalyptus globulus and Syzygium aro-maticum Essential Oils against Malaria Vector, Anopheles ste-phensi (Diptera: Culicidae) - Zahra Sheikh; Amir Amani; Hamid Reza Basseri; Seyed Hassan Moosa Kazemi; Mohammad Mehdi Sedaghat; Kamal Azam; Majid Azizi; Fatemehzahra Amirmohammadi (Tehran University of Medical Sciences, 2021)
Background: Mosquito species are highly considering as disease transmission as well as nuisance insects. One of the principal strategy to protect human from the mosquito bites is repellent agents. This study aimed to assess repellency of two organic essential oils, Eucalyptus globulus and Syzygium aromaticum from bites of malaria vector, Anopheles stephensi. Methods: The study was conducted in 2019-2020. The components of essential oils of E. globulus and S. aromaticum was determined using gas chromatography/mass spectrometry. The unfed female mosquitoes aged 2-5 d old were used in all experiments. In vivo Klun and Debboun module bioassays were utilized on human-volunteer skin. The essential oils at serial concentrations were used to find repellent efficacy against Anopheles landings and bites. To find the synergistic effect, four combinations of the essential oils were tested. Results: The main composition of E. globulus essential oil was 1,8-Cineol (78.20%), whereas that of S. aromaticum essential oil was 2-methoxy-3-(2-propenyl) (77.04%). Based on minimum effective dose (≤1% biting), 10% (v/v) of E. globulus showed high landing repellency (77.78%), whereas minimum effective dose of S. aromaticum at concentration of 1% had high landing repellency (88.89%). Among four combinations, the ratio of 1:1 of E. globulus (10%):S. aromaticum (1%) showed the most landing repellency (94.44%). Conclusion: The combinations of two essential oils had the most potential repellency effect against landing of mosquitoes. As essential oils are eco-friendly with less irritation for human skin, E. globulus and S. aromaticum essential oils are recommended as effective and safe mosquito repellents.